rdlc 2020
DOI: 10.7764/rdlc.19.3.407-421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the incorporation of residue of masonry on the properties of cementitious mortars

Abstract: This paper presents results of an experimental study of a residue of masonry (RM), sampled from a construction and demolition waste (CDW), added as a supplementary cementitious material (SCM) to partially replace up to 50% of Portland cement in the preparation of mortars. The pozzolanic activity (fixed lime and strength activity index), setting time, heat of hydration, the (autogenous and drying) shrinkage and compressive strength tests were carried out. The results show how the RM has a positive activity beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The decrease in water absorption rate from 28 days to 360 days in 25%- and 50%-substituted concretes for the control sample was 36.85%, 47.75%, and 58.79%, respectively. It was observed that the water absorption values of concrete specimens increased at the end of 28 days of curing time, while the water absorption values decreased at the end of 360 days of curing time due to the decrease in pore size in the matrix due to hydration and the pozzolanic reaction [ 90 ]. Moreover, 30% WBP substitution was reported to be the most effective ratio in reducing the water absorption of concrete.…”
Section: Durability Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in water absorption rate from 28 days to 360 days in 25%- and 50%-substituted concretes for the control sample was 36.85%, 47.75%, and 58.79%, respectively. It was observed that the water absorption values of concrete specimens increased at the end of 28 days of curing time, while the water absorption values decreased at the end of 360 days of curing time due to the decrease in pore size in the matrix due to hydration and the pozzolanic reaction [ 90 ]. Moreover, 30% WBP substitution was reported to be the most effective ratio in reducing the water absorption of concrete.…”
Section: Durability Propertiesmentioning
confidence: 99%
“…The total passing load was between 1196 C and 1742 C [ 56 ], indicating that all specimens had low chloride ion penetration according to ASTM C1202-97 [ 98 ]. Although the chloride penetration resistance of the control concrete was high in concrete specimens with 25% and 50% WBP substitution rate for 180 days, the chloride penetration value was 500 C, 375 C, and 410 C, respectively, compared to the control specimen as an effect of pore size reduction as a result of the pozzolanic reaction of WBP [ 90 ]. The chloride penetration values of 15%-, 30%-, and 45%-WBP-substituted concrete were 2181 C, 1922 C, 1427 C, and 1211 C, respectively, compared to the control specimen, and it was determined that there was a decrease in the total passing load [ 99 ].…”
Section: Durability Propertiesmentioning
confidence: 99%
“…These studies include investigation influence of different parameters( height-to-thickness ratio adherence, axial load, strengthening etc.) on the behavior of infill walls (Angel R, 1994;da Porto, Guidi, Verlato, & Modena, 2015;Demirel, yakut, & binici, 2018;Di Domenico, Ricci, & Verderame, 2019;André Furtado, Rodrigues, Arêde, & Varum, 2018;Sayın B., 2005;Silva, 2020;Valluzzi, da Porto, Garbin, & Panizza, 2014).…”
Section: Figurementioning
confidence: 99%